(untitled) - Norman, D. W. (Rome, 1994)
The book focus on the elements of the farming systems development (FSD) approach when handling issues related to soil conservation. The problem of soil erosion, sustainability and the farming systems research approach, and the use of FSD for soil conservation initiatives are reviewed. A conceptual framework for implementing the new soil conservation approach is described and outlined in a table, which is modelled on the format designed for FSD. Steps, tools and techniques used in implementing the new soil conservation approach are discussed
Keywords: Agricultural systems,Soil conservation